Pre-test metyrapone impairs memory recall in fear conditioning tasks: lack of interaction with β-adrenergic activity - Careaga, Mariella B. L.; Tiba, Paula A.; Ota, Simone M.; Suchecki, Deborah (Frontiers in Behavioral Neuroscience, 2015)
Cognitive processes, such as learning and memory, are essential for our adaptation to environmental changes and consequently for survival. Numerous studies indicate that hormones secreted during stressful situations, such as glucocorticoids (GCs), adrenaline and noradrenaline, regulate memory functions, modulating aversive memory consolidation and retrieval, in an interactive and complementary way. Thus, the facilitatory effects of GCs on memory consolidation as well as their suppressive effects on retrieval are substantially explained by this interaction. On the other hand, low levels of GCs are also associated with negative effects on memory consolidation and retrieval and the mechanisms involved are not well understood. The present study sought to investigate the consequences of blocking the rise of GCs on fear memory retrieval in multiple tests, assessing the participation of β-adrenergic signaling on this effect. Metyrapone (GCs synthesis inhibitor), administered 90 min before the first test of contextual or auditory fear conditioning, negatively affected animals’ performances, but this effect did not persist on a subsequent test, when the conditioned response was again expressed. This result suggested that the treatment impaired fear memory retrieval during the first evaluation. The administration immediately after the first test did not affect the animals’ performances in contextual fear conditioning, suggesting that the drug did not interfere with processes triggered by memory reactivation. Moreover, metyrapone effects were independent of β-adrenergic signaling, since concurrent administration with propranolol, a β-adrenergic antagonist, did not modify the effects induced by metyrapone alone. These results demonstrate that pre-test metyrapone administration led to negative effects on fear memory retrieval and this action was independent of a β-adrenergic signaling.